The Herbst appliance and the Activator: influence of the vertical facial pattern - Turnock Christopher; Woods Michael G. (Sciendo, 2016)
To compare the effects of the Herbst appliance and the Activator at the completion of two-phase treatment, with respect to the vertical facial pattern (VFP) and to identify possible predictors of treatment effect.